Considerations for refractive surgery in the glaucoma patient. Issue 4 (July 2017) - Ahmad, Meleha; Chocron, Isaac; Shrivastava, Anurag
Abstract : Purpose of review: Given the popularity of keratorefractive surgery, and an aging populous of patients who have undergone these procedures, there is an increasing need for updated management protocols. This is particularly relevant for patients with chronic progressive diseases such as glaucoma, due to the variety of related diagnostic and management challenges inherent to these diseases. Here, we will review the current literature to provide an update on the management of patients with glaucoma who are undergoing, or have had laser ablative refractive surgery. Preoperative testing and eligibility considerations, intraoperative factors, and postoperative observation and follow-up will be discussed. Recent findings: Intraoperative intraocular pressure (IOP) rise during flap creation is associated with low risk of acute complications, and furthermore do not appear to have significant long term effects. Modern technologies have improved our ability to determine accurate IOP after refractive surgery despite postoperative changes in corneal architecture. Furthermore, advances in structural imaging allow for earlier detection of even subtle glaucomatous nerve damage. Summary: Although glaucoma remains a relative contraindication to refractive surgery, it is a safe procedure for many patients with appropriate perioperative management and follow-up. Advancements in diagnostic modalities have allowed for earlier detection of glaucomatous disease, and subsequent earlier intervention when appropriate. Standardized diagnostic algorithms and rigorous perioperative assessment are critical to safe management of glaucoma patients undergoing refractive corneal surgery.